Rancang Bangun E-LKPD Berbasis Problem Based Learning Terintegrasi Nilai Tri Kaya Parisudha Pada Jenjang Sekolah Dasar - Putu Triska Prateja; Ni Nyoman Kurnia Wati; Ni Putu Candra Prastya Dewi (Jayapangus Press, 2026)
Learning motivation and cognitive achievement among Grade IV IPAS students at SD N 3 Kayuputih Melaka have declined, characterized by teacher-centered instruction, a lack of local culture based digital teaching materials, and a downward trend in formative scores with the average dropping from 77.2 to 69.3 and the proportion of students scoring below the minimum mastery threshold (KKTP) surging from 30% to 55%. This study aimed to design, develop, and evaluate an electronic student worksheet (E-LKPD) based on Problem Based Learning (PBL) and infused with Tri Kaya Parisudha (TKP) values ​​for Grade IV IPAS instruction. The study employed a Research and Development (R&D) approach using the ADDIE model, involving three expert validators, one teacher, six students in a small-group trial, and thirty students in a field trial; data were analyzed using descriptive statistics, the normalized N-Gain index, and a paired t-test. Validation results showed an average score of 89.45% (categorized as